Analisis Penerimaan Pengguna Platform Pembelajaran Virtual Learning Unesa (Vinesa) Menggunakan Task Technology Fit (TTF) Dan Technology Acceptance Model (TAM) Di Masa Pandemi COVID-19 - Indra Sulistyaningsih; Jaka Nugraha (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2022)
This study aims to examine the effect of Task Technology Fit (TTF) and Technology Acceptance Model (TAM) on student attitudes in learning supported by Vinesa during the COVID-19 pandemic. The COVID-19 pandemic demands various changes and innovations in the field of education and the implementation of the adaptive learning process continues to run well. The COVID-19 pandemic has pushed the world of education, especially universities, to change the learning process model from face-to-face learning in the classroom to online learning or distance learning. Vinesa is one of the applications used by the State University of Surabaya to support and manage online learning so that the teaching and learning process can still function properly during the COVID-19 pandemic. The data analysis method used is Structural Equation Modeling-Partial Least Squares (SEM-PLS). The sample size is 281 respondents from the Office Administration Education Study Program consisting of students in 2018, 2019, 2020, and 2021 at the State University of Surabaya. The results of this study indicate that task-technology fit (TTF) is an important role that influences students' attitudes towards online learning during the COVID-19 pandemic. Assignment technology suitability is considered when students try to use Vinesa to complete assignments. This study also proved that students responded with positive perceptions about task-technology suitability and had positive perceptions about ease of use (PEOU), perceived usefulness (PU), and behavioral intentions (BI) towards the use of Vinesa.